Numerical Analysis of Road Embankment Stability and Settlement Using Variations of Bamboo Chips and Fly Ash Mixtures - Vio Aditya Pratama Wijaya; Dian Purnamawati Solin; Karina Meilawati Eka Putri (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
Soft soil is one of the major challenges in road embankment construction due to its low bearing capacity, low shear strength, and high compressibility, which may lead to excessive settlement and slope instability. Therefore, an effective ground improvement method is required to enhance the mechanical performance of the subgrade soil. This study aims to analyze the stability and deformation behavior of road embankments constructed on soft soil stabilized with Fly Ash and reinforced with Bamboo Chips. The analysis was carried out using the Finite Element Method (FEM) based on the Mohr–Coulomb constitutive model. The numerical modeling compared untreated soil conditions with stabilized soil conditions using various percentages of Fly Ash and the addition of Bamboo Chips. Soil parameters were obtained from laboratory testing and incorporated into the numerical model. The analysis stages included embankment geometry modeling, load application, consolidation analysis, and safety factor analysis using the phi/c reduction method. The results indicate that the addition of Fly Ash and Bamboo Chips increased the embankment safety factor and reduced settlement compared to untreated soil conditions. Therefore, the combination of chemical stabilization using Fly Ash and reinforcement with Bamboo Chips has the potential to become an effective and sustainable alternative for soft soil improvement in road embankment construction in Indonesia. Contribution to Sustainable Development Goals (SDGs):SDG 9 : Industry, Innovation and InfrastructureSDG 11 : Sustainable Cities and CommunitiesSDG 12 : Responsible Consumption and ProductionSDG 13 : Climate ActionSDG 15 : Life on Land